Trichoderma-Induced Ethylene Responsive Factor MsERF105 Mediates Defense Responses in Malus sieversii - Ji, Shida; Liu, Zhihua; Wang, Yucheng (Frontiers in Plant Science, 2021)
Trichoderma can induce plant hormone signal pathways mediating plant defences, resulting in broad-spectrum resistance to phytopathogens. Herein, Malus sieversii seedlings were treated with Trichoderma biofertiliser and/or Alternaria alternata f. sp. mali (Aalm), and transcriptome analysis revealed significant differential expression. There was high similarity between the transcriptome expression profiles of Trichoderma-induced and A. alternata-infected M. sieversii samples for genes related to jasmonic acid (JA), ethylene (ET) and salicylic acid (SA) signalling pathways. Additionally, Trichoderma biofertiliser activated numerous disease-resistant genes (ERF, NAC, bHLH, and STK ) and defence response genes (DRP, ABC and HSP). Among transcription factors, members of the ERF family were the most differentially expressed (18 ERFs), indicating that they may be closely related to defence responses. Among ERFs, differential expression of MsERF105 was the most significant (upregulated 27.6-fold compared to controls). MsERF105 was heterologously expressed in PdPap poplar (Populus davidiana × P. alba var. Pyramidalis), and following infection with Alternaria alternata (Aal), transgenic PdPap-MsERF105s plants displayed lower malondialdehyde (MDA; downregulated 41.4%) and reactive oxygen species (ROS) levels, and higher reductase activities, especially superoxide dismutase (SOD; upregulated 77.5% compared to PdPap-ROK2 plants). Furthermore, the lesion areas of PdPap-MsERF105s leaves were significantly smaller (0.2%) than those of PdPap-ROK2 leaves (~26.0%), and the cell membrane integrity was superior for PdPap-MsERF105s leaves. Thus, MsERF105 enhanced the resistance of PaPap poplar to Aal, presumably because MsERF105 activates the expression of PR1 and PDF1.2. In conclusion, Trichoderma biofertiliser modulated the differential expression of numerous disease resistance genes and defence response genes in M. sieversii in response to pathogen attack, and MsERF105 played important roles in this process.